2018
DOI: 10.1002/cbdv.201800208
|View full text |Cite
|
Sign up to set email alerts
|

Juniperus phoenicea var. turbinata (Guss.) Parl. Leaf Essential Oil Variability in the Balkans

Abstract: In the present work, the leaf essential oil from 97 individuals of Juniperus phoenicea var. turbinata (Guss.) Parl. from the Balkan Peninsula was analyzed. The essential oil was dominated by monoterpene hydrocarbons (45.5 - 71.8%), of which α-pinene was the most abundant in almost all of the samples (38.2 - 55.8%). Several other monoterpenes and sesquiterpenes were also present in relatively high abundances in samples such as myrcene, δ-3-carene, β-phellandrene, α-terpinyl acetate, (E)-caryophyllene and germac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This is consistent with the results obtained earlier by other authors, who also showed significant variation within the J. turbinata group, with a low level of variability in J. phoenicea s.s., stating that the range of J. turbinata is sufficiently large but fragmented and discontinuous (Quézel 1980;Browicz 1982;Boratyński et al 2009). Several authors have analysed the essential oil chemical variability within the J. turbinata group around the Mediterranean (Adams et al 2014;Rajčević et al 2018) andin Algeria (Bekhechi et al 2012). Three chemotypes were found, and several geographic patterns within the species were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results obtained earlier by other authors, who also showed significant variation within the J. turbinata group, with a low level of variability in J. phoenicea s.s., stating that the range of J. turbinata is sufficiently large but fragmented and discontinuous (Quézel 1980;Browicz 1982;Boratyński et al 2009). Several authors have analysed the essential oil chemical variability within the J. turbinata group around the Mediterranean (Adams et al 2014;Rajčević et al 2018) andin Algeria (Bekhechi et al 2012). Three chemotypes were found, and several geographic patterns within the species were recorded.…”
Section: Introductionmentioning
confidence: 99%